Sarana Promosi Dan Informasi Sebagai Video Profile SMK Yuppentek 2 Curug Kabupaten Tangerang - Desy Apriani; Rosdiana Rosdiana; Asriyani Asriyani (UNIVERSITAS RAHARJA, 2018)
Multimedia has now penetrated all over the world even difficult to be separated from everyday life. Multimedia in education provides learning techniques so that maximum results. Prospective students are expected to make it easier for them to determine how students can receive information quickly and effectively. promotion using computer technology has improved better so that it follows technological developments. But currently the agency does not have promotional video media regarding the profile of education to the wider community. preproduction, production and postproduction stages. In order to produce quality video profile information communication designs using Adobe Photoshop CS6, Adobe Premier CS6 and Adobe Corel Video Studio X5.